Basic Makeup Vocational Skills Program for Learners with Hearing Impairment at Special Senior High School Level - Muanis, Anelia; Aprilia, Imas Diana (Journal of ICSAR, 2024)
This research is motivated by the learning of cosmetology skills that have not been optimal for children with hearing impairments in SKh Negeri 02 Serang City. This condition is allegedly the result of inappropriate provision of skills that have not considered talent interests and teacher competence that is not qualified in cosmetology skills. The purpose of this study is to formulate a basic makeup skills program for students with hearing impairments at the senior high school level. The approach used in this research is research and development with exploratory mixed method research design and at the program trial stage researchers use experimental methods with a single subject research design (A-B-A).  The results of the pilot test of the basic makeup program that has been made show that the program improves students' abilities from an initial score of 25% to a final score of 68%.